The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1089/gyn.2010.0117
|View full text |Cite
|
Sign up to set email alerts
|

Resection of a Giant Ovarian Mucinous Cystadenoma with Intraoperative Drainage

Abstract: Background: Giant ovarian tumors are now rarely encountered, because of the wide availability of medical care, and most cases are benign. Case: A rare case of a giant ovarian cystadenoma in a 41-year-old woman, with such severe abdominal distension that she could not walk, is reported. Her abdominal girth was 141 cm. The patient was 151 cm tall and weighed 92.6 kg. Computed tomography (CT) showed a large, multilocular, cystic tumor that occupied the whole abdomen. The preoperative diagnosis was malignant ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…14 Since then, Abe et al identified 22 cases of ovarian tumors reported in the literature measuring between 47 kg and 134 kg. 11 The cysts were benign in 72.7% of cases and borderline or malignant in 27.2% of cases. 11,15 In a literature review, Einenkel et al found an overall malignancy rate of 37% in giant ovarian cysts.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…14 Since then, Abe et al identified 22 cases of ovarian tumors reported in the literature measuring between 47 kg and 134 kg. 11 The cysts were benign in 72.7% of cases and borderline or malignant in 27.2% of cases. 11,15 In a literature review, Einenkel et al found an overall malignancy rate of 37% in giant ovarian cysts.…”
Section: Discussionmentioning
confidence: 94%
“…11 The cysts were benign in 72.7% of cases and borderline or malignant in 27.2% of cases. 11,15 In a literature review, Einenkel et al found an overall malignancy rate of 37% in giant ovarian cysts. 12 The differential diagnosis can be difficult to establish in the presence of abundant ascites.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations